Making Pedagogic Sense of Design Thinking in the Higher Education Context - Beligatamulla Gnanaharsha; Rieger Janice; Franz Jill; Strickfaden Megan (De Gruyter, 2019)
This paper explores the educator experience and sense-making of design thinking pedagogy in the higher education context. Design thinking has become a pedagogical phenomenon in higher education due to its widespread relevance across many disciplines. Some studies discuss design thinking as a pedagogy in the educational context; however, there is a lack of empirical research to understand the educator perspective on design thinking pedagogy. Three design thinking educators who have had more than fifteen years of teaching experience were interviewed to explore their experiences. The data from these individual in-depth, semi-structured interviews were analysed employing Interpretative Phenomenological Analysis (IPA). One super-ordinate theme; capability building for everyone, and four subordinate themes; developing a participatory approach towards world issues; developing an open, explorative attitude; developing creative ability; and developing an ethical mindset were identified. From these findings, the paper argues that design thinking educators have the basis for a pedagogical rationale that transcends disciplinary boundaries and provides common ground for collaboration and on-going development of design thinking pedagogy as an emerging field in education.